2021
DOI: 10.1038/s41398-021-01719-7
|View full text |Cite
|
Sign up to set email alerts
|

Cortical complexity in world trade center responders with chronic posttraumatic stress disorder

Abstract: Approximately 23% of World Trade Center (WTC) responders are experiencing chronic posttraumatic stress disorder (PTSD) associated with their exposures at the WTC following the terrorist attacks of 9/11/2001, which has been demonstrated to be a risk factor for cognitive impairment raising concerns regarding their brain health. Cortical complexity, as measured by analyzing Fractal Dimension (FD) from T1 MRI brain images, has been reported to be reduced in a variety of psychiatric and neurological conditions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 126 publications
5
17
1
Order By: Relevance
“…Seven out of nine functional hubs differ between WTC-PTSD and non-PTSD in our study were located in the right hemisphere (Figure 1, Table 2), suggesting lateralization of the association between WTC-PTSD and centrality. These results align with our previous study in this cohort demonstrating anatomical changes with strong lateralization in the right hemisphere across several brain areas 6 . Lateralization may be due to specific functions of the right hemisphere such as the continuous interchange of information with the amygdala.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Seven out of nine functional hubs differ between WTC-PTSD and non-PTSD in our study were located in the right hemisphere (Figure 1, Table 2), suggesting lateralization of the association between WTC-PTSD and centrality. These results align with our previous study in this cohort demonstrating anatomical changes with strong lateralization in the right hemisphere across several brain areas 6 . Lateralization may be due to specific functions of the right hemisphere such as the continuous interchange of information with the amygdala.…”
Section: Discussionsupporting
confidence: 93%
“…During these months on the pile, WTC responders were exposed to both traumatic event and a number of pollutants including lead, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and dioxins that all together might have played a role in the anatomical and functional changes observed 3639 . These changes and their significant association with long-term WTC exposure involve only specific cortical and subcortical brain regions such as the whole hippocampus and its subfields 5 , parahippocampal gyrus, amygdala, and finally frontal and parietal brain regions 6 that seem more vulnerable to experience at the WTC site. These results might be explained by the fear-conditioning mechanism and novel neurocircuitry models 911 that suggest the triggering event, in this case WTC responders experienced during rescue and recovery efforts, targets brain areas known to be involved in PTSD, i.e., the parahippocampus and amygdala.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies of those involved in the rescue and recovery efforts after 11 September 2011 (WTC Responders) indicate that WTC exposures may be associated with neuroinflammation, neurodegeneration and increased cognitive impairment, and in turn, with increased risk of Alzheimer’s disease and related dementia in subsequent years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In particular, cognitive impairment among WTC Responders has been extensively studied using validated instruments for measuring objective cognitive dysfunctions including the Montreal Cognitive Assessment (MoCA, [ 9 ]), and in-depth assessments using well-established blood-based biomarkers and neuroimaging markers of cognitive impairment [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. These reports also include a large number of association studies of cognitive impairment with WTC exposures and associated mental health conditions among WTC Responders.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also found PTSD to be associated with cognitive impairment in both military and non-military populations [ 4 , 5 , 7 , 10 , 37 , 38 , 39 , 40 , 41 , 42 ]. Extensive research has been carried out on cognitive functioning and decline in the WTC Responder population including on self-reported cognitive complaints [ 10 , 41 ], an association with PTSD [ 4 , 5 , 7 ], dust exposure [ 1 ], as well as biomarkers and neuroimaging studies [ 2 , 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%